Assessment of Serum Metalloendopeptidase level in Patients with Double Diabetes - Hassan , Hussein Jawad; Mohammad, Taghreed Uloom; Hameed, Ekhlas Khalid (AL-Kindy College Medical Journal, 2023)
Background: Double diabetes is the term used to describe situations in which a patient exhibits characteristics that are a combination of type 1 and type 2 Diabetes Mellitus. Metalloendopeptidase or Neprilysin is membrane-bound metallopeptidase. It has a wide range of physiological function and a variety of substrates. It has a significant impact on the proteolytic functions of the kidney, cardiovascular health, immunological response, cell proliferation, and fetal development. It also has a preventative effect on the onset of type 2 diabetes, obesity, and cancer. Objective: The study aims to assess the level of MEP in patients with double diabetes and determine its predictive value in the diagnosis of double diabetes. Subjects and Methods: Eighty participants were divided into two groups for this study. 40 patients with double diabetes made up the first group (G1), whereas 40 age- and gender-matched apparently healthy subjects made up the second group (G2), which served as the control group. ELISA was used to measure the serum’s metalloendopeptidase level. For the measurement of HbA1c, whole blood was used. The measurement of insulin, blood glucose, and lipid profile were performed using serum. The HOMA test measured insulin resistance. Results: This study revealed a significant elevation in serum metalloendopeptidase levels in patients with DD (p value < 0.05). The ROC curves analysis for serum metalloendopeptidase level showed the area under the curve (AUC) of serum metalloendopeptidase (pg/mL) was 0.992. Conclusions: Serum metalloendopeptidase level could be used as a novel biomarker in patients with double diabetes.